(untitled) (Bangladesh Journal of Medicine, 2023)
Backgroud: To assess the effectiveness of intralesional Platelet Rich Plasma (PRP) therapy for the treatment of deQuervain`s tenosynovitis. Methods: The study was randomized controlled trial conducted in the Department of Physical Medicine and Rehabilitation, BSMMU, Dhaka, from April 2020 to March 2021.A total of 54 patients with lateral wrist pain were randomly allocated into two groups and were given interventions. Twenty six patients in group A were treated with 3 ml of autologous platelet rich plasma injection alongthe inflamed tendon sheath of Abductor Pollicis Longus (APL) and Extensor Pollicis Brevis (EPB) tendons while patients in group B were given conventional therapy in the form of rest, ice pack application, analgesics and anti-edema measures for 2 weeks and physical therapy in the form of soft tissue massage.Pain was assessed in VAS. Functional improvement was assessed by Patients Rated Wrist Evaluation (PRWE) scale. Twenty six patients in group A and twenty five patients in group B had completed the six month follow up schedule. Results: The mean age of the participants in group A and group B were 38.23 (± 10.47) and 40.76 (± 8.05) years respectively where >80.0% patients in both groups were female. From 1st month, the VAS scores significantly reduced in group A compared to group B which persisted up to 6 months (p<0.001). In group A, 85.0% reduction of pain score and in group B, 71.8% reduction of pain score was achieved after 6 month of treatment. From 1st month, the PRWE scores significantly reduced more in group A compared to group B (p=0.021) which persisted up to 6 months (p<0.001). In group A, 89.1% functional improvement while in group B, 72.6% functional improvement was achieved after 6 month of treatment. Conclusion: Intra-lesional platelet-rich plasma reduces pain and improves function in patients with de Quervain`s tenosynovitis. Bangladesh J Medicine 2023; 34(2): 93-97